Sizing Up Extracellular DNA: Instant Chromatin Discharge From Cells When Placed in Serum-Free Conditions - Spyrou, Giannis; Appelgren, Daniel; Rosén, Anders; Ingelsson, Björn (Frontiers in Cell and Developmental Biology, 2020)
How do you wash cells? Three out of four of our colleagues use experimental procedures during everyday lab-bench work that can severely impair data interpretation depending on how cells are handled. We show here that a subpopulation (2-3%) of human leukocytes immediately induce a yet unclassified lytic cell death, concomitant with discharge of chromatin entities and cell elimination, when placed in protein-free solutions (i.e. PBS and HBSS). DNA release was not restricted to hematopoietic cells but occurred also in HEK293T cells. Albumin, fetal bovine serum, polyethylene glycol, and Pluronic F-68 supplements prevented chromatin discharge. Expelled chromatin was devoid of surrounding membranes but maintained its original nuclear shape, although ~10 times enlarged. These structures differed from DNA appearance after osmotic or detergent-induced cell lysis. Besides sounding a cautionary note to the neutrophil extracellular trap (NET) research community, in which ~50% of all published studies used protein-free media for NET-formation, our study also provides a rapid tool for analysis of chromatin organization.